Implementasi Metode Kriptografi Advanced Encryption Standard (AES) untuk Proteksi Pesan Audio - Sihombing, Marto; Sitompul, Juliana Naftali; Putri, Tia Anggia (MEANS (Media Informasi Analisa dan Sistem), 2019)
This study is to solve the problem Cryptographic techniques used to protect and maintain the confidentiality of audio messages by changing audio messages into audio messages that cannot be played by doing the encryption process and can be played back after the audio message is decrypted. To protect audio messages, it is used in the process of encrypting and decrypting audio messages using the Advanced Encryption Standard (AES) method. The Advanced Encryption Standard (AES) uses symmetric key block passwords with varying key sizes of 128 bits, 192 bits, and 256 bits. The Advanced Encryption Standard (AES) method used is 128 bit key size and there are 10 rounds in the process of encryption and decryption. Audio messages that have been encrypted using the Advanced Encryption Standard (AES) method cannot be played by parties who do not know the key to encrypt and decrypt the audio message. Audio messages are protected and protected from irresponsible parties who want to damage or just listen to the audio message.